Synthesis and Characterization of Titanium Dioxide Nanoparticles in Wood Protection Application - Kah Yee., Tan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Wood is an indispensable tool for human due to its aesthetic value, its properties and availability functions. However, wood will be degraded by microbes or termites. There were many studies for wood protection in the aspect of termite resistance, decay resistance, antibacterial, antifungal and chemical leaching. For example, wood timber is also being treated with inorganic biocides (copper based complex with chrome or arsenate). Their release could cause pollution to the environment. As alternatives, environmentally friendly organic biocide (e.g. emulsion of organic biocides and copper salt) and engineered nanomaterial have been investigated. In this study, the titanium dioxide nanoparticles synthesized were non-uniform in sizes or irregular shapes and, not well-dispersed and the mean sizes of dialyzed titanium dioxide nanoparticles were in the range of 6 nm to 10 nm. Titanium dioxide nanoparticles produced were impregnated within the Dyera costulata (Jelutong) wood blocks through vacuum impregnation, the results showed there was low leaching rate of titanium dioxide nanoparticles leached out from the wood block over two weeks which was detected by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES).